How to Develop the Algebraic Thinking of Students in Mathematics Learning (Jurusan Matematika FMIPA UNNES, 2020)
The aim of this article is to explain how to develop the algebraic thinking of students in mathematics learning. Algebraic thinking is ability of students to analyze, make generalization, solve problems, predict, justify, and prove as well as model some situations. It is an essential and fundamental element of mathematical thinking. But apparently, based on the results of previous literature studies, obtained some facts that algebra is one of the materials that is difficult to be mastered by students. This article is written based on several scientific journals. This article is going to explain some strategies for developing algebraic thinking skills. The strategies are learning using 7E learning cycle model (elicit, engagement, exploration, explanation, elaboration, evaluation, and extend), learning using technology (video-game; software that are spreadsheet, geogebra, group explorer, pearson’s, MyMathLab, digital mathematics environments, SimCal), learning using manipulatives, learning using multiple representation that is realistic approach (orientation, exploration, internalization, and evaluation), and also through government regulation that is early learning.